Controlling the Synthesis Protocols of Palladium‐Based Nanostructures for Enhanced Electrocatalytic Oxidation of Carbon Monoxide: A Mini‐Review - Adewale K. Ipadeola (12699590) (2023)
Pd‐based nanostructures are endowed with impressive catalytic features for alcohol‐based fuel cells, however, their poisoning by carbon monoxide (CO) is a great barrier to large‐scale utilization of such fuel cells as alternative power sources. The need to optimize the electrochemical CO oxidation (COOxid) of Pd‐based nanostructures in various electrolytes has attracted much attention in the last decade, so it is important to provide a timely update on this area of research. This mini‐review highlights the most recent advances in controlling some synthesis methods of Pd‐based nanostructures and their morphologies for enhanced electrocatalytic COOxid in different electrolyte conditions in the last three years. Finally, the main challenges for commercially viable Pd‐based nanostructures for electrochemical COOxid are discussed, highlighting the future perspectives and providing promising solutions for practical COOxid application. Other Information Published in: ChemElectroChem License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/celc.202300363